Partial characterization of bean and maize root peroxidases and their ability to crosslink potato protein - Glušac, Jovana; Isaschar-Ovdat, Sivan; Fishman, Ayelet; Kukavica, Biljana (Archives of Biological Sciences, 2019)
Paper description: Globular proteins are resistant to crosslinking in enzyme-catalyzed reactions due to the complex structure of protein. We show for the first time that peroxidases from maize and bean roots are capable of crosslinking the globular protein patatin. In the crosslinking reaction phenolic compounds served as mediators. Enzymatic crosslinking of globular proteins provides additional insight into protein-protein interactions and modification of the biophysical structure of the protein. Abstract: Two fractions of Class III peroxidases (POX; EC 1.11.1.7), soluble and ionically bound to the cell wall, were partially purified from bean and maize roots and characterized. According to the measured Km, both the soluble and ionically bound to the cell wall fractions of POX had high affinity for H2O2 and the high specificity for caffeic acid. Approximate molecular weights of POX in their tertiary (native) structure were determined by modified sodium dodecyl sulfate (SDS) polyacrylamide gel electrophoresis (PAGE). Proteomic analysis resolved the identity and pI of different enzyme bands. The ability of maize and bean soluble peroxidase to crosslink native potato proteins was evaluated. The results obtained by SDS-PAGE showed that both POX enzymes were capable of crosslinking potato protein, in particular patatin, a globular protein, with and without the presence of H2O2. To investigate the possible role of phenolic compounds in facilitating crosslinking, commercial horseradish peroxidase (HRP) with/without the addition of caffeic acid was used to crosslink potato protein. Information provided here could be useful for the purification of POX from maize and bean roots and for examination of protein-protein interactions. https://doi.org/10.2298/ABS181016011G Received: October 16, 2018; Revised: January 1, 2019; Accepted: February 18, 2019; Published online: March 4, 2019 How to cite this article: Glušac J, Isaschar-Ovdat S, Fishman A, Kukavica B. Partial characterization of bean and maize root peroxidases and their ability to crosslink potato protein. Arch Biol Sci. 2019;71(2):293-303.